Compreender a experiência de lutas dos pais de crianças autistas pelo direito a educação no município de Altamira-PA - SILVA, Dilcilene Reis da (2023)
The research refers to a bibliographic-exploratory research study that sought to understand the struggle of parents of children with Autistic Spectrum Disorder for the right to education in the municipality of Altamira-Pá. We know that the biggest challenge today is to provide a quality education, without distinction, and for that, it must guarantee the rights of people diagnosed with autism through laws and movements to which it comes to ensure more inclusive and respectful spaces and also their rights. It proposed as a general objective: to understand the experience of struggles of parents of autistic children for the right to education. And as a methodological path, a qualitative approach was used with a bibliographic approach with an exploratory character, being them, a survey of sources for the composition of the collection published in the last five years, contained in the SciELO Journal portal, academic Google and safe sources that contain materials related to autism, public policies and inclusive education. To enrich this research, it was necessary to obtain data, a script for an open interview with three questions through the Word and WhatsApp program; this and due to the atypical moment we are experiencing as a result of the Corona virus pandemic. It is concluded how important the participation of parents, the school community and the support of people around the child with autism is from the beginning, in the diagnosis, as well as in the treatment and in the evolution of educational and social practices.